Turbulent Energy Conversion Associated With Kinetic Microinstabilities in Earth's Magnetosheath - Harry C. Lewis; Julia E. Stawarz; Lorenzo Matteini; Luca Franci; Kristopher G. Klein; Robert T. Wicks; Chadi S. Salem; Timothy S. Horbury; Joseph H. Wang (Geophysical Research Letters, 2024)
Abstract Plasma in Earth's magnetosheath rarely experiences interparticle collisions, so kinetic microinstabilities are thought to contribute to regulating the plasma thermodynamics. Instabilities excite waves and redistribute free energy in velocity space, reducing free energy in the velocity distribution function (VDF). Using 24 hr of data spread over 163 intervals of in situ magnetosheath observations by Magnetospheric Multiscale (MMS), we investigate signatures of energy conversion where the turbulent dynamics have locally distorted the VDFs into non‐Maxwellian shapes, in the context of electron and ion temperature anisotropy driven instabilities. We find enhanced average energy conversion into the particles along instability boundaries, suggesting turbulence plays a role in redistributing free energy. In so doing, we quantify the energetics associated with unstable conditions for both species. This work provides insight into the open question of how specific plasma processes couple into the turbulent dynamics, ultimately leading to energy dissipation and particle energization in collisionless plasmas.